The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/acn3.50836
|View full text |Cite
|
Sign up to set email alerts
|

Probing axons using multi‐compartmental diffusion in multiple sclerosis

Abstract: Objects The diffusion‐based spherical mean technique (SMT) provides a novel model to relate multi‐b‐value diffusion magnetic resonance imaging (MRI) data to features of tissue microstructure. We propose the first clinical application of SMT to image the brain of patients with multiple sclerosis (MS) and investigate clinical feasibility and translation. Methods Eighteen MS patients and nine age‐ and sex‐matched healthy controls (HCs) underwent a 3.0 Tesla scan inclusive of clinical sequences and SMT images (iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 29 publications
(42 reference statements)
3
18
0
Order By: Relevance
“…Accordingly, despite the MC-SMT model does not allow the quantification of non-monoexponential behavior to describe the deviation of diffusion displacement from the Gaussian profile specifically ( Jensen et al, 2005 ), a significant decrease of μFA and ƒ in have been demonstrated for different degrees of brain and SC tissue damage in MS compared with normal WM tissue ( By et al, 2018 , Lakhani et al, 2020 ). Furthermore, such microscopic features seem to be able to distinguish MS lesions with more axonal damage from the lesions that are hyperintense in T2-weighted sequences ( Bagnato et al, 2019 , Bonet-Carne et al, 2019 ), identified as black-holes in T1-spin echo sequences ( van Walderveen et al, 1998 ). When compared with the observation of black holes, the use of quantitative diffusion metrics increases the accuracy and reproducibility of the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, despite the MC-SMT model does not allow the quantification of non-monoexponential behavior to describe the deviation of diffusion displacement from the Gaussian profile specifically ( Jensen et al, 2005 ), a significant decrease of μFA and ƒ in have been demonstrated for different degrees of brain and SC tissue damage in MS compared with normal WM tissue ( By et al, 2018 , Lakhani et al, 2020 ). Furthermore, such microscopic features seem to be able to distinguish MS lesions with more axonal damage from the lesions that are hyperintense in T2-weighted sequences ( Bagnato et al, 2019 , Bonet-Carne et al, 2019 ), identified as black-holes in T1-spin echo sequences ( van Walderveen et al, 1998 ). When compared with the observation of black holes, the use of quantitative diffusion metrics increases the accuracy and reproducibility of the results.…”
Section: Discussionmentioning
confidence: 99%
“…The MC-SMT model computes a multi-compartment domain, encompassing extra-axonal and intra-axonal water diffusion spaces, and microscopic diffusion tensor maps to estimate distinct local tissue properties ( Kaden et al, 2016 ). In MS, MC-SMT seems to be able to distinguish chronic black-holes and thus, lesions with greater tissue damage from hyperintense T2 lesions ( Bagnato et al, 2019 , Bonet-Carne et al, 2019 ), and this approach can detect reductions in the apparent axon volume fraction in the spinal cord (SC) ( By et al, 2018 ). Therefore, SMT-derived tissue features could be used as biomarkers to quantify the heterogeneous mechanisms involved in MS lesion pathogenesis in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…In brains 22 and spinal cords 23 of patients with MS, V ax and D ax (brain only 22 ) differed between lesions and normal-appearing WM. Decreased values of V ax were also observed in normalappearing WM compared with normal WM of healthy controls (spinal cord only 23 ).…”
Section: Histopathologic Validationmentioning
confidence: 92%
“…Clinical Application. Only 2 studies investigating the feasibility and applicability of SMT in the brains 22 and spinal cords 23 of patients with MS have been performed thus far. The authors reported acquisition times between $18 minutes 23 (single-section C-spine, 1.25 Â 1.25 Â 10 mm resolution, 2 b-shells, with 32 and 64 directions) and $22 minutes (full brain coverage, 0.4 Â 0.4 Â 2 mm resolution, 90 directions).…”
Section: Histopathologic Validationmentioning
confidence: 99%
See 1 more Smart Citation